Protection from ultraviolet radiation - Lucas, R.; Neale, R.; Gies, P.; Slevin, Terry (Oxford University Press, 2017)
© Oxford University Press 2018. Strategies to protect against excessive exposure to ultraviolet (UV) radiation are required to reduce the risk of melanoma, non-melanoma skin cancers, and eye diseases. The programs that have been most effective in reducing sun exposure involve combinations of education intended to change individual beliefs and behavior, tools for personal protection from the sun, and the creation of environments that support sun protection. Specific strategies include community-wide media campaigns, school-based interventions, counseling by healthcare providers about sun protection, education on the appropriate use of protective clothing and sunscreen, and policies to restrict access to indoor tanning beds. Sun protection strategies are most effective when introduced in childhood, although interventions in adulthood can also reduce skin cancer incidence. There are health risks of complete sun avoidance, so a balance between inadequate and excessive sun protection is necessary.